Skills and Returns to Education in the Russian Federation - World Bank (World Bank, Washington, DC, 2020)
The objective of this ASA was ‘to develop policy recommendations for the Russian Federation based on a detailed analysis of the returns to education and identification of feasible pathways for robust growth in Russia’s human capital wealth’. The second part of identifying feasible pathways was perhaps stated too ambitiously. The study does include elements of possible future strategy work with priority regions as well as a potentially very useful idea for individual universities and colleges.